CORRELATION BETWEEN CUTTING TEMPERATURES AND METALLURGICAL PROPERTIES OF COMPACTED GRAPHITE CAST IRONS IN THE END MILLING PROCESS - da Silva, L. R. R.; Machado, A. R. (Revista de Engenharia Térmica, 2021)
In the search for more energy-efficient internal combustion engines, the automotive companies keep pushing the working temperatures and pressures of the engines, leading to more extreme working conditions and so the necessity of new materials. Among the most promising materials for the new generations of engines is the compacted graphite cast iron, which is more wear-resistant than aluminum and tougher than gray cast iron. However, this combination of properties also leads to decreased machinability, increasing production costs and, therefore, their market competitiveness. This paper evaluated the correlation of mechanical and metallurgical properties and the cutting power and surface roughness of three grades of compacted graphite cast iron with the cutting temperature in the end milling process under different two different feed rates and cutting speeds. This analysis showed that the temperatures near the cutting zone are closely correlated to the material’s mechanical properties, machining power, and resulting roughness. These results indicate that thermographic images are a good indicator of the overall correlation between the changes in material properties and the most usual machinability output parameters.